The Role of Augmented Reality in The Online Shopping Experience: How Can Clothing Brands Use Mobile Augmented Reality Applications to Offer a More Immersive Shopping Experience to Their Customers?. - Hanene HAMMAMI (Communications of International Proceedings, 2023)
This study aims to explore the potential of augmented reality (AR) in enhancing the online shopping experience for customers of clothing brands. It investigates the effective utilization of mobile AR applications by clothing brands to offer a more immersive and interactive shopping experience. This research fills a void in the literature concerning the specific application of AR in the clothing industry, making it a crucial contribution. The methodology involves a comprehensive review of relevant literature on AR in online shopping and its impact on customer experience. Subsequently, an analysis of existing mobile AR applications used by clothing brands is conducted to provide insights into the immersive shopping experience they offer. The findings of this study reveal the benefits and challenges associated with implementing AR in online shopping, along with best practices for clothing brands adopting this technology. Its originality lies in exploring how AR can enhance the online shopping experience for customers, particularly in the clothing industry. Unlike previous research that briefly addressed AR in marketing, this study focuses specifically on its application in the context of clothing brands. In conclusion, this study provides practical insights for clothing brands considering the implementation of AR in their marketing strategy. The derived findings and recommendations assist brands in understanding the potential, benefits, and challenges of AR, while offering guidance for successful implementation. By addressing these research gaps, this study contributes to the existing body of knowledge on AR and its impact on online shopping.
Keywords: Augmented reality; Online shopping; Customer experience; Clothing brands.